An electrocatalytic membrane-assisted process for hydrogen production from H2S in Black Sea: Preliminary results. (29th June 2015) - Ipsakis, D.; Kraia, Tz.; Marnellos, G.E.; Ouzounidou, M.; Voutetakis, S.; Dittmeyer, R.; Dubbe, A.; Haas-Santo, K.; Konsolakis, M.; Figen, H.E.; Güldal, N.O.; Baykara, S.Z.
Abstract: The feasibility of hydrogen production by the decomposition of H2 S in an electrocatalytic membrane reactor for the exploitation of H2 S contained in Black Sea water is investigated. A micro-structured electrochemical membrane reactor with a proton-conducting ceramic membrane is considered for processing gaseous H2 S diluted (1 vol.%) in H2 O mixtures. Y-doped barium zirconate (BaZr0.85 Y0.15 O3−δ ) is employed as solid electrolyte. Ceria supported transition metal (Co, Ni, Fe, Cu) catalysts and LaCrO3 composites are explored as anode materials and La0.6 Sr0.4 Co0.2 Fe0.8 O3−δ perovskite type oxides are used as cathode electrodes. Preliminary results concern materials preparation and characterization of the catalytic performance of anodic electrode materials. Co/CeO2 composites show excellent H2 S conversion and stability performance in wet and dry atmospheres at 873–1123 K. Presence of water has a beneficial effect on the H2 formation, in accordance with thermodynamics. The overall process starting from H2 S containing sea water to H2 generation in the membrane reactor and H2 SO4 production in a sequential step is simulated and its energy balance is discussed. Graphical abstract: Highlights: An electro-catalytic membrane reactor is proposed to convert H2 S/H2 O to H2 . Results related to reactor development and cell materials evaluation are presented. Co/CeO2 exhibited promising activity/stability under "real" conditions. An energetic analysis for H2 production from Black Sea-H2 S/H2 O is presented.